Small RNA sequencing identified miR-3180 as a potential prognostic biomarker for Chinese hepatocellular carcinoma patients - Sun, Libo; Zhou, Hansheng; Zhao, Xiaofei; Zhang, Haitao; Wang, Yan; Li, Guangming (Frontiers in Genetics, 2023)
MicroRNAs (miRNAs) and their target genes are aberrantly expressed in many cancers and are linked to carcinogenesis and metastasis, especially among hepatocellular carcinoma (HCC) patients. This study sought to identify new biomarkers related to HCC prognosis using small RNA sequencing from the tumor and matched normal adjacent tissue of 32 patients with HCC. Eight miRNAs were downregulated and 61 were upregulated more than twofold. Of these, five miRNAs, hsa-miR-3180, hsa-miR-5589-5p, hsa-miR-490-5p, hsa-miR-137, and hsa-miR-378i, were significantly associated with 5-year overall survival (OS) rates. Differential upregulation of hsa-miR-3180 and downregulation of hsa-miR-378i in tumor samples supported the finding that low and high concentrations of hsa-miR-3180 (p = 0.029) and hsa-miR-378i (p = 0.047), respectively, were associated with higher 5-year OS. Cox regression analyses indicated that hsa-miR-3180 (HR = 0.08; p = 0.013) and hsa-miR-378i (HR = 18.34; p = 0.045) were independent prognostic factors of poor survival. However, high hsa-miR-3180 expression obtained larger AUCs for OS and progression-free survival (PFS) and had better nomogram prediction than hsa-miR-378i. These findings indicate that hsa-miR-3180 may be associated with HCC progression and could serve as a potential biomarker for this disease.